Ambulatory Subspecialty Visits in a Large Pediatric Primary Care Network - Vernacchio, Louis (Blackwell Science Inc, 2012)
OBJECTIVE: To determine patterns of subspecialty utilization within a pediatric primary care network. DATA SOURCES/STUDY SETTING: Paid claims from a large not-for-profit health plan for patients of The Pediatric Physicians' Organization at Children's, a network of private pediatric practices affiliated with Children's Hospital Boston. PRINCIPAL FINDINGS: The subspecialty visit rate was 1.01 visits per subject-year. In 2007, 56.8 percent of subjects had no subspecialty visits, whereas 4.2 percent had ≥5 visits; the corresponding figures in 2008 were 54.1 and 4.5 percent, respectively. The most frequently visited subspecialties were Ophthalmology, Orthopedics, Dermatology, Otorhinolaryngology, and Allergy/Immunology. Visit rates varied sevenfold by practice. CONCLUSIONS: Wide practice variability in pediatric subspecialty utilization suggests an opportunity for reducing unnecessary visits. Better integration between primary care and the most commonly used subspecialties will be needed to meaningfully reduce unnecessary visits and enhance value.